Localized Bone Augmentation and Implant Site Development-Review with a case - Koirala, Pramod Kumar; Pradhan, S; Gorkhali, RS (Journal of Nepalese Prosthodontic Society, 2019)
Guided bone regeneration (GBR) has been used for the regeneration of bone in conjunction with the placement of dental implants, for augmentation of resorbed alveolar crests, and to treat localized ridge deformities. It is based on the principle of protecting bone regeneration against overgrowth of tissues formed by rapidly proliferating non-osteogenic cells. In this case, the space created by the Titanium mesh supported platelet rich fibrin membrane was filled by tissues with features of newly formed bone. No residual bone defects were observed and an increase of the alveolar width and height was observed. No untoward effects on bone regeneration were observed except membrane exposure after 4 and 1/2months. This case shows a satisfactory result concerning GBR technique or implant site development.